Production, purification and characterisation of oligosaccharides from olive tree pruning autohydrolysis - Cara, Cristóbal (2012)
The production of oligosaccharides (OS) by olive tree pruning autohydrolysis in the range 170–230 °C was studied. The best results in terms of maximum yield of OS along with a low amount of byproducts were obtained at 180 °C. After purification by preparative gel filtration chromatography a range of OS-fractions with average degree of polymerisation (DP) from 25 to 3 was selected for further characterisation. Gluco-and xylooligosaccharides were the predominant OS in these fractions. OS yields in the range 80–90% were obtained for fractions with average DP between 25 and 7, practically free of low molecular compounds. Both OS total yields and xylooligosaccharides proportion decreased for lower DP fractions while monosaccharides and other products concentrations increased. OS production and the recovery of other high value compounds can be envisaged as an interesting contribution to develop an olive-biomass biorefinery.